Lab-on-a-chip for analysis of blood - Abdul bari, Hayder A.
With the growing popularity of microfluidics devices, medical science is also progressing its way through fast and efficient microfabricated diagnosis devices. Blood testing and analysis are primary and necessary steps in medical diagnosis; hence smart and fast microdiagnostic devices are considered essential. Blood is the most vital fluid, containing all the essential minerals and vitamins, and it can be a carrier for other biological pathogens such as a bacterium, virus, or other microorganism, making it the perfect subject for analysis for an accurate diagnosis. This chapter introduces and discusses microfluidics technology’s influence on the diagnosis of blood diseases. The chapter starts with a comprehensive introduction of the rapid development of microfluidics technology and its applications followed by sections that detail the microfluidics science fundamentals, lab-on-chip, and microfabrication techniques. It then explains specifically the influence of microfluidics technology in the development of different blood testing techniques and methods with a more comprehensive focus on its applications in sexually transmitted diseases.